Disposal and management of used batteries from households in Hue city: current status and proposed solutions for improvement - Phạm, Khắc Liệu; Lê, Quý Hiền (Hue University Journal of Science: Natural Science, 2025)
Batteries, especially non-rechargeable ones, are commonly used in households. Waste batteries are classified as hazardous components in household solid waste. This paper presents the results of a survey on the current status of household battery generation and disposal and the awareness of Hue city’s residents towards waste battery disposal and management and proposes some improvement solutions. The results of the survey of 109 households in 8 selected wards and communes of Hue City reveal that the battery generation rate is 0.248 kg/household/year or 0.054 kg/capita/year, corresponding to a total amount of about 30.4 tons/year or 83 kg/day for the entire Hue City. Most people are aware of the hazardous effects of used batteries and the need to separate batteries from household waste. However, over 88% of people still maintain the habit of disposing of batteries with household waste. Some barriers to proper battery disposal (sorting, storing separately, transferring to collection units) include the small amount of waste, the negligible trade value of waste batteries, and the lack of awareness of waste collectors. Several solutions to improve the disposal and management of used batteries from households have been proposed from the perspective of state management and operation of collection and treatment enterprises.